Light‐chain and transthyretin cardiac amyloidosis in severe aortic stenosis: prevalence, screening possibilities, and outcome. (20th February 2020) - Nitsche, Christian; Aschauer, Stefan; Kammerlander, Andreas A.; Schneider, Matthias; Poschner, Thomas; Duca, Franz; Binder, Christina; Koschutnik, Matthias; Stiftinger, Julian; Goliasch, Georg; Siller‐Matula, Jolanta; Winter, Max‐Paul; et al.
Abstract: Aims: Concomitant cardiac amyloidosis (CA) in severe aortic stenosis (AS) is difficult to recognize, since both conditions are associated with concentric left ventricular thickening. We aimed to assess type, frequency, screening parameters, and prognostic implications of CA in AS. Methods and results: A total of 191 consecutive AS patients (81.2 ± 7.4 years; 50.3% female) scheduled for transcatheter aortic valve replacement (TAVR) were prospectively enrolled. Overall, 81.7% underwent complete assessment including echocardiography with strain analysis, electrocardiography (ECG), cardiac magnetic resonance imaging (CMR), 99m Tc‐DPD scintigraphy, serum and urine free light chain measurement, and myocardial biopsy in immunoglobulin light chain (AL)‐CA. Voltage/mass ratio (VMR; Sokolow–Lyon index on ECG/left ventricular mass index) and stroke volume index (SVi) were tested as screening parameters. Receiver operating characteristic curve, binary logistic regression, and Kaplan–Meier curve analyses were performed. CA was found in 8.4% of patients ( n = 16); 15 had transthyretin (TTR)‐CA and one AL‐CA. While global longitudinal strain by echo did not reliably differentiate AS from CA‐AS [area under the curve (AUC) 0.643], VMR as well as SVi showed good discriminative power (AUC 0.770 and 0.773, respectively), which was comparable to extracellular volume by CMR (AUC 0.756). Also, VMR and SVi were independently associated with CA by multivariate logistic regression analysis ( P = 0.016 and P = 0.027, respectively). CA did not significantly affect survival 15.3 ± 7.9 months after TAVR ( P = 0.972). Conclusion: Both TTR‐ and AL‐CA can accompany severe AS. Parameters solely based on ECG and echocardiography allow for the identification of the majority of CA‐AS. In the present cohort, CA did not significantly worsen prognosis 15.3 months after TAVR.